Is there a role for functional MRI for the assessment of extracapsular extension in prostate cancer? - Sertdemir, Metin; Weidner, Anja; Schönberg, Stefan; Häcker, Axel; Weiß, Christel; Hausmann, Daniel; Attenberger, Ulrike (Anticancer research, 2018)
Background/Aim: Exctracapsular extension (ECE) in prostate cancer has a high impact on treatment decision. MRI might predict presence of ECE non-invasively. Patients and Methods: Triplanar T2w-sequences, DWI (diffusion weighted imaging) and DCE (dynamic contrast-enhanced imaging) of 34 patients with PCa were analyzed to prior prostatectomy. Sensitivity (SS) and specificity (SP) of T2w, apparent diffusion coefficient (ADC), plasma flow (PF) and mean transit time (MTT) normalized by PCa/normal tissue ratio for prediction of CI (capsular infiltration)/ECE were determined by area-under-the-receiver-operating-characteristics analysis. Results: SS/SP for detecting ECE was 29/85. AUC (area under the curve) of ECE cases was 0.98/0.92/0.69 (cut-off-ratios 3.2/0.51/0.46), SS 93/100/86% and SP 95/80/50% for PF-/MTT-/ADC-ratios, respectively. PF- and MTT-ratios between CI and without CI/ECE differed significantly (PF, p<0.0001; MTT, p=0.0134) with SS/SP 84/89% for PF and SS/SP 52/100% for MTT-ratios. No significant differences regarding ADC-ratios were identified. Conclusion: ECE/CI can be assessed by quantitative DCE analysis with great diagnostic confidence and higher specificity than ADC.
Gesehen am 29.04.2020